Differential rates of cesarean delivery by maternal geographical origin: a cohort study in France - Morgane Linard (BMC Pregnancy and Childbirth, 2019)
Abstract Background In many Western countries, higher rates of cesarean have been described among migrant women compared to natives of receiving countries. We aimed to estimate this difference comparing women originating from France and Sub-Saharan Africa (SSA), identify the clinical situations explaining most of this difference and assess whether maternal origin was independently associated with cesarean risk. Methods The PreCARE prospective multicenter cohort study was conducted in 2010–2012 in the north Paris area. Our sample was restricted to 1500 women originating from Sub-Saharan Africa and 2206 from France. Profiles of cesarean section by maternal origin were described by the Robson classification. Independent associations between maternal origin and 1) cesarean before labor versus trial of labor, then 2) intrapartum cesarean versus vaginal delivery were assessed by logistic regression models to adjust for other maternal and pregnancy characteristics. Results Rates of cesarean for women originating from France and SSA were 17 and 31%. The Robson 5A category “unique uterine scar, single cephalic ≥37 weeks” was the main contributor to this difference. Within this category, SSA origin was associated with cesarean before labor after adjustment for medical risk factors (adjusted odds ratio [aOR] = 2.30 [1.12–4.71]) but no more significant when adjusting on social deprivation (aOR = 1.45 [0.63–3.31]). SSA origin was associated with cesarean during labor after adjustment for both medical and social factors (aOR = 2.95 [1.35–6.44]). Conclusions The wide difference in cesarean rates between SSA and French native women is mainly explained by the Robson 5A category. Within this group, medical factors alone do not explain the increased risk of cesarean in SSA women.